COVID19: an announced pandemic (2020)
A severe upper respiratory tract syndrome caused by the new coronavirus has now spread to the entire world as a highly contagious pandemic. The large scale explosion of the disease is conventionally traced back to January of this year in the Chinese province of Hubei, the wet markets of the principal city of Wuhan being assumed to have been the specific causative locus of the sudden explosion of the infection. A number of findings that are now coming to light show that this interpretation of the origin and history of the pandemic is overly simplified. A number of variants of the coronavirus would in principle have had the ability to initiate the pandemic well before January of this year. However, even if the COVID-19 had become, so to say, ready, conditions in the local environment would have had to prevail to induce the loss of the biodiversity’s “dilution effect” that kept the virus under control, favoring its spillover from its bat reservoir to the human target. In the absence of these appropriate conditions only abortive attempts to initiate the pandemic could possibly occur: a number of them did indeed occur in China, and probably elsewhere as well. These conditions were unfortunately present at the wet marked in Wuhan at the end of last year.